Examining the influence of store environment in hedonic and utilitarian shopping - Cristina Calvo-Porral; Jean-Pierre Lévy-Mangin (Administrative Sciences, 2021)
Much of the literature on the attractiveness and pleasantness of retail stores has focused on the critical influence of store atmosphere or ambient attributes, which influence customer satisfaction and store choice. However, little is known about the environmental cues that influence customers' satisfaction in different shopping contexts. In this context, the present research aims to answer the following questions: 'Are the store atmospheric variables equally relevant in hedonic and utilitarian shopping?'; and further: 'Does the influence of store environment on customer satisfaction vary depending on the type of shopping?'. For this purpose an empirical research is developed through PLS Structural Equation Modeling (PLS-SEM) based on data obtained from hedonic (n = 210) and utilitarian (n = 267) shopping contexts. Results indicate that customers perceive differently store atmospherics in utilitarian and in hedonic shopping. More precisely, findings report that customer satisfaction is driven by internal ambient and merchandise layout in hedonic shopping contexts; while the external ambient and the merchandise layout are major atmospheric cues in utilitarian shopping. Interestingly, store crowding does not influence customers' satisfaction. This study provides a deeper understanding into the specific store attributes that influence customer satisfaction, which could be used by retailers to differentiate themselves from competitors.
Keywords: 350; store atmosphere; retail; utilitarian shopping; hedonic shopping; store crowding